PENGARUH PENAMBAHAN PAKAN ALTERNATIF DARI BAHAN MAKROALGA (Gracilaria spDAN Ulva lactuca) DALAM PELET TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Ndjandji Karipi Wuhi; Yulianus Linggi; Priyo Santoso (Nusa Cendana University, 2019)
A research has been conduct to know the effect of both Gracillaria sp and Ulva lactuce flour on Nile, Oreochromis niloticus, growth rate. These flour was substitute in to pellets till the allotted amount of each treatment and reshaped as it was subsequently. The study using 2 x 2 x 3 factorial design based on completely random design. Adding the flours of gracillaria, ulva and its combination were the first factor, and the 10 to 20% amount of each flour were the second factor. The results show that the Nile’s SGR was higher, 1.69% day-1, on 20% of ulva flour treament. The following grade of Nile’s SGR are 1.67, 1.53, 1.45, 1.32, and 1.16 % day-1 for adding 10% gracillaria, 20% combination, 10% ulva, 10% combination, 20% gracillaria respectively. We suggest that both Gracillaria sp and Ulva sp would raise up the growth of Nile but the flour proportion is a specific for each kind of feed. The Nile growth rate of ulva’s treatment was significant different to gracillaria’s treatment. Keywords: Ulva, Gracillaria, Feed, Growth, Nile